Paratránsito y accesibilidad: más allá de la movilidad urbana en el área metropolitana de Cochabamba - Méndez, Lucas A. (2024)
Urban transport services in Bolivia are characterized by their informality, self-management, atomization, reduced quality, as well as a high capacity for route multiplication, the main link with urban sprawl. However, an analysis of the level of accessibility that this mode of service allows in Cochabamba shows that it is a highly efficient service under this indicator. The level of accessibility that paratransit allows contributes to the reduction of inequalities and articulation of the peripheries to the opportunities offered by the city.